3D Geovisualizations and Participatory Land-Use Planning – Planners’ Perspectives from Finland - Linkola, Hannu; Fagerholm, Nora; Eilola, Salla (Informa UK Limited, 2025)
Our article discusses the use of 3D geovisualizations in participatory planning in Finnish municipalities. The data from a survey and interviews among the municipality-level planners is analyzed from the perspectives of three discursive spaces: representational, experiential, and institutional. Our study shows that 3D geovisualizations are regarded as attractive tools, but their usage is sporadic, and the benefits are mostly evaluated on the basis of technical and representational qualities. Rather than increasing the role of citizens in planning, the new technologies partially reinforce the role of planners, albeit entailing the potential to support interaction with citizens.